Development of urban public transport in Latin America and the world (ECLAC SantiagoCL, 1994)
Traces the development of public transport from the seventeenth century under headings such as technology, urban, sub-urban and metropolitan or underground system. Looks at the problems of transport such as congestion and cost.
Bibliography: p.68-69